PELATIHAN PEMANFAATAN MINYAK JELANTAH MENJADI SABUN CUCI SEBAGAI SOLUSI RAMAH LINGKUNGAN OLEH MAHASISWA KKN MBKM UNRI - Nabilla Eka Putri; Allyvia Febriolla; Clara Nindhita; Kinanti Dwi Pratiwi; Meisya Adila; Novia Ningsih; Fatiya Nabila Utami; Zahra Tuljannah; Zakiya Rahma Indra; Resma Wahyuni (JURNAL AKADEMIK PENGABDIAN MASYARAKAT, 2024)
Used cooking oil is oil that has been reused multiple times and can have harmful effects on health if consumed, as well as causing soil pollution if disposed of on the ground. The purpose of conducting this socialization and training activity on the utilization of used cooking oil into soap is to raise awareness among the community about the dangers of used cooking oil for health and the environment. The method used is socialization along with training. The target partners for this activity are the PKK mothers, consisting of 15-20 members. The outcome of this activity is to enhance the knowledge and skills of the PKK mothers in processing used cooking oil into laundry soap, with the hope that this activity can be implemented independently.